3
$\begingroup$

I would really appreciate some help on this problem that I have been working on.
It's a power series question. I have to find the interval of convergence for this power series.

The power series is:

$$\sum_{n=0}^\infty n(x-9)^n$$

The work I have done so far is:

I used the Ratio Test to find the radius of convergence

$\lim_{n\to \infty} |{a_{n+1}\over a_{n}}| = \lim_{n\to \infty}|{(n+1)(x-9)^{n+1}\over n(x-9)^n}| = \lim_{n\to \infty} |(x-9){n+1\over n} = lim_{n\to \infty} |x-9| = |x-9|$

According to the Ratio Test, If $|x-9| \lt 1,$ then the series will converge

I deduced that the radius, R = 9, within 1 number at each side. So the boundaries are x = 8 and x = 10. I know that at the radius the series in convergent. Now I have to test the boundaries, to check whether the series converges or diverges at those particular points.

This is the part I am having trouble with. I can't figure out if the series converges or diverges at x = 8 and x = 10. Help would be really appreciated.

At x = 8, $\sum_{n=0}^\infty n(x-9)^n$ = ?

At x = 10,$\sum_{n=0}^\infty n(x-9)^n$ = ?

$\endgroup$
  • $\begingroup$ Do the terms of the series go to zero on the boundaries? $\endgroup$ – robjohn Apr 1 '14 at 4:16
  • $\begingroup$ At $x=8$, $\sum_{n=0}^\infty n(x-9)^n = \sum_{n=0}^\infty (-1)^n n = 0 -1 + 2 - 3 + 4 - 5 + \cdots$. $\endgroup$ – Stephen Montgomery-Smith Apr 1 '14 at 4:30
1
$\begingroup$

You have convergence for $|x-9|<1 \Rightarrow -1 < x-9 < 1 \Rightarrow 8<x<10$.

Here the radius does not include the end points, but that is not enough.

One can show $\sum_{n=0}^{\infty}nx^n$ only converges for $|x|<1$.

Now your done since $|10-9| = 1, |8-9|= 1$.

$\bf{Additional}$: One can check divergence by $n^{th}$ term test.

$\endgroup$
0
$\begingroup$

First of all, notice that $$\sum_{n=0}^\infty n(x-9)^n=\sum_{n=1}^\infty n(x-9)^n=(x-9)\sum_{n=1}^\infty n(x-9)^{n-1}$$ The last sum is the derivative, with respect to $x$ of $$\sum_{n=1}^\infty (x-9)^{n}$$ which is geometric progression. Then $$\sum_{n=1}^\infty (x-9)^{n}=-\frac{x-9}{x-10}$$ and then $$\sum_{n=0}^\infty n(x-9)^n=\frac{x-9}{(x-10)^2}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.